1996
DOI: 10.1074/jbc.271.45.28492
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Is a Modulator of Tobacco and Mammalian Catalases

Abstract: Salicylic acid (SA) plays a key role in the establishment of resistance to microbial pathogens in many plants. The discovery that SA inhibits catalase from tobacco led us to suggest that H 2 O 2 acts as second messenger to activate plant defenses. Detailed analyses of SA's interaction with tobacco and mammalian catalases indicate that SA acts as an electron donor for the peroxidative cycle of catalase. When H 2 O 2 fluxes were relatively low (1 M/min or less), SA inhibited catalase, consistent with its suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
160
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(166 citation statements)
references
References 71 publications
3
160
0
3
Order By: Relevance
“…1A). 19,33 SA has affinity for various forms of heme proteins such as native form of catalase 8, 9 and ascorbate peroxidase, 15 Compound II of HRP 18 and SBP, 32 and Compound III of HRP. 19 We can expect that SA may interact with native form of plant peroxidases.…”
Section: Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). 19,33 SA has affinity for various forms of heme proteins such as native form of catalase 8, 9 and ascorbate peroxidase, 15 Compound II of HRP 18 and SBP, 32 and Compound III of HRP. 19 We can expect that SA may interact with native form of plant peroxidases.…”
Section: Proposed Modelmentioning
confidence: 99%
“…[1][2][3] Early studies have indicated that SA is an active signal accompanying oxidative burst by which development of systemic acquired resistance (SAR) against a wide range of pathogens is induced, as reviewed in several articles by our group. [2][3][4][5][6] In 1990s, it has been proposed that SA signaling paths leading to SAR require the accumulation of ROS derived from H 2 O 2 , 7 based on the observation that SA binds and inhibits 2 types of H 2 O 2 -detoxifying enzymes, namely catalase 8, 9 and ascorbate peroxidase. 10 In addition to these passive modes of ROS production by SA, more active modes of SA action involving extracellular peroxidase and NADPH oxidase that directly generates ROS in the presence of SA was reported later.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SA radicals derived from the catalase oxidation-reduction cycle could facilitate lipid peroxidation, which in turn activates PR-1 genes in tobacco cells (14). It is important to note that APX is a much better oxidant of SA than is catalase.…”
Section: Sa Is Not An Inhibitor Of Apx-mentioning
confidence: 99%
“…Apparently, in different plants under certain environmental conditions other products of detoxification of SA may also be formed. Further in vivo studies are necessary to define the mechanism of detoxification of SA by APX.It has been reported that SA radicals derived from the catalase oxidation-reduction cycle could facilitate lipid peroxidation, which in turn activates PR-1 genes in tobacco cells (14). It is important to note that APX is a much better oxidant of SA than is catalase.…”
mentioning
confidence: 99%
See 1 more Smart Citation